(untitled) (Лучшие интеллектуальные исследования, 2025)
Annotation: This paper examines the concepts of equivalence and adequacy in the translation of scientific and technical terms, using the theoretical frameworks of Newmark, Koller, and Vinay & Darbelnet. It explores the nature of terminological correspondence between source and target languages and discusses the challenges of preserving meaning, function, and form. Through examples from engineering, IT, and medical texts, the paper compares strategies that aim at formal, dynamic, and functional equivalence. The study concludes by suggesting flexible strategies tailored to the purpose, text type, and reader knowledge. Annotatsiya: Ushbu maqolada ilmiy va texnik terminlarni tarjima qilishda ekvivalentlik va adekvatlik tushunchalari tahlil qilinadi. Mualliflar Newmark, Koller hamda Vinay va Darbelnetning tarjima nazariyalari asosida manba va tarjima tillari o‘rtasida terminologik moslikni ta’minlashda uchraydigan muammolarni yoritadilar. Muhandislik, axborot texnologiyalari va tibbiyot matnlaridan olingan misollar orqali formal, dinamik va funksional ekvivalentlik strategiyalari solishtirib chiqiladi. Tadqiqot xulosasida matn turi, maqsadi va auditoriya bilim darajasiga mos strategiyalarni tanlash taklif etiladi. Аннотация: В статье рассматриваются понятия эквивалентности и адекватности при переводе научной и технической терминологии. Анализ проводится в рамках теорий Ньюмарка, Коллера и Вине с Дарбельне, с акцентом на трудности сохранения значения, функции и формы терминов. На примерах из инженерии, ИТ и медицины сравниваются стратегии формального, динамического и функционального эквивалента. В заключение предлагаются гибкие переводческие подходы в зависимости от цели текста, его жанра и уровня подготовки целевой аудитории.